Two fatty acid‐binding proteins expressed in the intestine interact differently with endocannabinoids. (28th April 2020) - Lai, May Poh; Katz, Francine S.; Bernard, Cédric; Storch, Judith; Stark, Ruth E.
Abstract: Two different members of the fatty acid‐binding protein (FABP) family are found in enterocyte cells of the gastrointestinal system, namely liver‐type and intestinal fatty acid‐binding proteins (LFABP and IFABP, also called FABP1 and FABP2, respectively). Striking phenotypic differences have been observed in knockout mice for either protein, for example, high fat‐fed IFABP‐null mice remained lean, whereas LFABP‐null mice were obese, correlating with differences in food intake. This finding prompted us to investigate the role each protein plays in directing the specificity of binding to ligands involved in appetite regulation, such as fatty acid ethanolamides and related endocannabinoids. We determined the binding affinities for nine structurally related ligands using a fluorescence competition assay, revealing tighter binding to IFABP than LFABP for all ligands tested. We found that the head group of the ligand had more impact on binding affinity than the alkyl chain, with the strongest binding observed for the carboxyl group, followed by the amide, and then the glycerol ester. These trends were confirmed using two‐dimensional 1 H– 15 N nuclear magnetic resonance (NMR) to monitor chemical shift perturbation of the protein backbone resonances upon titration with ligand. Interestingly, the NMR data revealed that different residues of IFABP were involved in the coordination of endocannabinoids than those implicated for fatty acids, whereas the same residues of LFABP were involved for both classes of ligand. In addition, we identified residues that are uniquely affected by binding of all types of ligand to IFABP, suggesting a rationale for its tighter binding affinity compared with LFABP.